2012
DOI: 10.1523/jneurosci.2302-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Localized Calcineurin Confers Ca2+-Dependent Inactivation on Neuronal L-Type Ca2+Channels

Abstract: Excitation-driven entry of Ca2+ through L-type voltage-gated Ca2+ channels controls gene expression in neurons and a variety of fundamental activities in other kinds of excitable cells. The probability of opening of CaV1.2 L-type channels is subject to pronounced enhancement by cAMP-dependent protein kinase (PKA), which is scaffolded to CaV1.2 channels by A-kinase anchoring proteins (AKAPs). CaV1.2 channels also undergo negative autoregulation via Ca2+-dependent inactivation (CDI), which strongly limits Ca2+ e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 59 publications
6
64
0
Order By: Relevance
“…Past and present work clearly shows that the phosphatase CaN must be targeted near the LTCC to provide efficient and specific activation of NFAT signaling via channel Ca 2+ influx (Li et al, 2012; Oliveria et al, 2007; Zhang and Shapiro, 2012). Yet sequestering CaN within the LTCC nano-domain also promotes a robust phosphatase mediated negative-feedback on PKA-enhanced channel activity, both through suppression of peak current amplitude and promotion of Ca 2+ -dependent inactivation (CDI) of neuronal LTCCs (Dittmer et al, 2014; Oliveria et al, 2007; Oliveria et al, 2012). Indeed, while previous studies in hippocampal neurons demonstrated that LTCC current and Ca 2+ influx can be enhanced by activation of cAMP-PKA signaling (Hoogland and Saggau, 2004; Kavalali et al, 1997), the degree of PKA enhancement of LTCC current is constrained by AKAP79/150-anchored CaN activity (Oliveria et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past and present work clearly shows that the phosphatase CaN must be targeted near the LTCC to provide efficient and specific activation of NFAT signaling via channel Ca 2+ influx (Li et al, 2012; Oliveria et al, 2007; Zhang and Shapiro, 2012). Yet sequestering CaN within the LTCC nano-domain also promotes a robust phosphatase mediated negative-feedback on PKA-enhanced channel activity, both through suppression of peak current amplitude and promotion of Ca 2+ -dependent inactivation (CDI) of neuronal LTCCs (Dittmer et al, 2014; Oliveria et al, 2007; Oliveria et al, 2012). Indeed, while previous studies in hippocampal neurons demonstrated that LTCC current and Ca 2+ influx can be enhanced by activation of cAMP-PKA signaling (Hoogland and Saggau, 2004; Kavalali et al, 1997), the degree of PKA enhancement of LTCC current is constrained by AKAP79/150-anchored CaN activity (Oliveria et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal membrane depolarization initiates NFAT signaling by triggering Ca 2+ influx through LTCCs to activate calmodulin (CaM) molecules tethered to the intracellular C-terminal domain of the channel (Peterson et al, 1999; Zuhlke et al, 1999). Ca 2+ -CaM promotes rapid activation of CaN, which is recruited to the LTCC through AKAP79/150 anchoring (Oliveria et al, 2007; Oliveria et al, 2012; Zhang and Shapiro, 2012). Organization of the LTCC-AKAP-CaN macromolecular complex at the plasma membrane arises in part through additional interaction of modified leucine zipper (LZ) motifs on AKAP79/150 and the C-terminal tail of Ca V 1.2 (Hulme et al, 2003; Oliveria et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms targeting CaN to different subcellular locales exist and have been shown to be an important part of CaN signaling. For example, AKAP79/150 targets CaN to the post-synaptic density where it regulates ionotropic glutamate receptors and L-type Ca 2ϩ channels (52)(53)(54)(55). It is therefore possible that similar scaffolding interactions target CaN to the OMM to amplify Drp1 Ser-656 dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…At present, it is universally recognized that regard less of the neuron or terminal type, L type calcium channels are the target of various phosphatase-kinase and voltage dependent regulations [27,[32][33][34], although, in motor terminals, inhibitory phosphatase actions dominate resulting in the inhibition of L type calcium channels [10,20]. However, in cases where L type calcium channels are disinhibited, CaMKII activity is generally present in the cell; quite often, it is a form of positive feedback for the maintenance of the functioning of a channel itself [21,30,35].…”
Section: Discussionmentioning
confidence: 99%